Taking compact NMR to monitoring real reactions in large‐scale chemical industries—General considerations and learnings from a lab‐scale test case. (30th June 2020) - Nestle, Nikolaus; Lim, Zi Jian; Böhringer, Tobias; Abtmeyer, Sarah; Arenz, Sven; Leinweber, Felix C.; Weiß, Thomas; von Harbou, Erik
Abstract: The considerations for use of compact nuclear magnetic resonance in a large‐scale industrial environment clearly differ from those in academic and educational settings and even from those in smaller companies. In the first part of this article, these differences will be discussed along with the additional requirements that need to be fulfilled for successful applicability in different use cases. In the second part of the article, outcomes from different research activities aiming to fulfill these requirements will be presented with a focus on an online reaction‐monitoring study on a lab‐scale nucleophilic chlorination reaction. Abstract : A prototype compact nuclear magnetic resonance (NMR) spectrometer equipped with a Dewar for long‐time measurements on samples with elevated temperature and a flow cell was validated for application in reaction monitoring, and a nucleophilic chlorination reaction was studied as an example. Furthermore, some general considerations on the possible future role of compact NMR in chemical industry are made.